2014
DOI: 10.1093/mnras/stu1904
|View full text |Cite
|
Sign up to set email alerts
|

The ESO UVES Advanced Data Products Quasar Sample – IV. On the deficiency of argon in DLA systems

Abstract: In this work, we study argon abundances in the interstellar medium of high-redshift galaxies (2.0 z abs 4.2) detected as Damped Lyα absorbers (DLA) in the spectra of background quasars. We use high-resolution quasar spectra obtained from the ESO-UVES advanced data products (EUADP) database. We present 3 new measurements and 5 upper limits of Ar i. We further compiled DLAs/sub-DLA data from the literature with measurements available of argon and α-capture elements (S or Si), making up a total of 37 systems, i.e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
1
15
2
Order By: Relevance
“…As AGN and quasars are key factors for galaxy evolution directly as essential ingredients in the galaxy formation recipe and indirectly as probes of intervening material, for example, of chemical evolution (Smith et al 1979;Pettini et al 1994;Lu et al 1996;Zafar et al 2014;Berg et al 2016;Krogager et al 2019), it is very important to get a complete census of AGN, in general, and of quasars in particular. The early work of Sandage (1965) already demonstrated that the original radio-selection of quasars only reveals a minority of the underlying population (the radio-loud quasars).…”
Section: Introductionmentioning
confidence: 99%
“…As AGN and quasars are key factors for galaxy evolution directly as essential ingredients in the galaxy formation recipe and indirectly as probes of intervening material, for example, of chemical evolution (Smith et al 1979;Pettini et al 1994;Lu et al 1996;Zafar et al 2014;Berg et al 2016;Krogager et al 2019), it is very important to get a complete census of AGN, in general, and of quasars in particular. The early work of Sandage (1965) already demonstrated that the original radio-selection of quasars only reveals a minority of the underlying population (the radio-loud quasars).…”
Section: Introductionmentioning
confidence: 99%
“…The physical nature of DLAs also influences their gas phase abundances, including the role of ionizing sources (D'Odorico 2007;Ellison et al 2010;Zafar et al 2014b) or the amount of dust (e.g. Pettini et al 1994;Kulkarni et al 1997;Akerman et al 2005;Krogager et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We have modelled these systems in detail using the spectral simulation code CLOUDY to understand the physical conditions in highredshift DLAs. The 3 DLAs for which we study the physical environment are the systems at: zabs = 2.3377 towards LBQS 1232+0815 (Srianand, Petitjean & Ledoux 2000;Varshalovich et al 2001;Ivanchik et al 2010;Balashev et al 2011;Zafar et al 2014), zabs = 2.41837 towards SDSS J143912.04+111740.5 (Noterdaeme et al 2008b;Srianand et al 2008), and zabs = 2.6265 towards FBQS J081240.6+320808 (Prochaska, Howk & Wolfe 2003;Jorgenson et al 2009;Tumlinson et al 2010;Jorgenson et al 2010). Typically, DLAs may constitute absorption arising from more than one cloud along the line-of-sight.…”
Section: Introductionmentioning
confidence: 99%